ISTANA SEBAGAI SENTRAL STRUKTUR TATA KOTA (Studi Kasus pada Lima Kota Kerajaan di Kalimantan Barat dan Kalimantan Timur) - Atmojo, Bambang Sakti Wiku (Balai Arkeologi Kalimantan Selatan, 2007)
There are many city in Kalimantan that was an old site of kingdom which own palace remainder from the past. There are the palace which located in the central of other buildings, in the end of the building line, in the riverbank, and in the river intersection or road intersection. Many factor which influence palace location among others natural condition, and social political conditions. Nevertheless, the palace still central form in the urban affair structure and kingdom political structure.